Hydrogenolysis of alginic acid over mono and bimetallic ruthenium/nickel supported on activated carbon catalysts with basic promoters. Issue 9 (7th August 2020) - Yang, Seungdo; Kim, Hyungjoo; Kim, Do Heui
Abstract : Hydrogenolysis of alginic acid, derived from macroalgae, was performed over Ru–Ni supported on activated carbon catalyst using NaOH as basic promoter to produce glycols. Abstract : Hydrogenolysis of alginic acid, derived from macroalgae, over Ru, Ni and Ru–Ni supported on activated carbon catalysts was performed in a batch reactor using NaOH, CaCO3, Ca(OH)2, and Mg(OH)2 as basic promoters. Among the promoters used, NaOH provides the highest carbon efficiency and yield of glycols, such as ethylene glycol and 1, 2-propanediol. In addition, various organic acids such as lactic acid, glycolic acid, and formic acid were produced in the form of salts. The hydrogenolysis of potential intermediates such as sorbitol, mannitol, lactic acid, and glycolic acid demonstrated direct conversion of alginic acid to glycols without sugar alcohols or organic acids as reaction intermediates. Furthermore, Ru–Ni bimetallic catalysts as a function of the Ni/Ru molar ratio were used to increase the yield of and selectivity to glycols. The highest yield of glycols, 24.1%, was obtained when the Ni/Ru molar ratio was 1 : 1, due to the enhanced interaction between Ru and Ni based on H2 -TPR.